PENGEMBANGAN PERMAINAN WATER RINGBALL DALAM AKTIVITAS LUAR KELAS PADAPEMBELAJARAN PENJASORKES DI S EKOLAH DASAR NEGERI BANJARSARI 1 KECAMATAN GAJAH KABUPATEN DEMAK TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The problem in this research is how to models the development of water ringball games in outdoor activities atpenjasorkes learning in Banjarsari 1 Elementary School at Gajah Subdistrict of Demak Regency in 2013. Thepurpose of this research is a produce of water ringball games in outdoor activities to students in class V and VIBanjarsari 1 Elementary School at Gajah Subdistrict of Demak Regency in 2013. The data was collected usinga questionnaire from expert evaluation, as well as using field observations and the results of the questionnaireby the students. The data analysis technique used is descriptive percentages. From a small group test resultsobtained data of expert evaluation, penjas expert 80% (good), learning experts 76% (good), the resultsquestionnaire by small group test on psychomotor aspects average 88,5%, cognitive aspects 96,5%, affectiveaspects 89,5%, and the final average of questionnaire on small group test results obtained 91,5% (excellent).From a large group test results obtained data of expert evaluation, penjas expert 90,67% (excellent), learningexperts 90,67% (excellent), the results questionnaire by large group test on psychomotor aspect average 91,4%,cognitive aspects 98,2%, affective aspects 93,8%, and the final average of questionnaire on large groups testresults obtained 94,47% (excellent).